TECHNIQUES OF PAIN REDUCTION IN THE NORMAL LABOR PROCESS : SYSTEMATIC REVIEW - Anita, Wan (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Pain during labor is a physiological condition commonly experienced by most maternity mothers. Labor pain is a subjective experience caused by uterine muscle ischemia, withdrawal and traction of uterine ligaments, ovarian traction, fallopian tubes and lower uterine distension, pelvic floor muscles and perineum. The pain in labor arises from psychic responses and physical reflexes. The purpose of this Systematic review is to look at effective methods for reducing pain in the labor process so that it can be used as an alternative method of reducing pain in patients who will give birth. This review systematic review of the published artike through google scholar site with 17 journals reviewed. In an effort to reduce labor pain there are various methods that can be used in providing midwifery care in the process of childbirth. Based on this systematic review it can be concluded that many methods of pain reduction that can be used in reducing labor pain are counter pressure and abdominal lifting, hypnobirthing, religious and murottal music, classical music and local music, relaxation, compress, warm ginger drink, acupressur , TENS, account and aromatherapy.